Navigating Tradition and Territory: The Islamic Business Ethics of Minangkabau Traders in Negeri Sembilan, Malaysia - Muslim Marpaung; Irma Suryani Lubis; Syahrial Arif Hutagalung; Yessi Kurnia Arjani Manik; Jufri Naldo (KURAS Institute, 2025)
This study explores Islamic economics and business anthropology with a focus on the commercial ethics of the Minangkabau diaspora in Negeri Sembilan, Malaysia. The central problem addressed is the growing challenge faced by diaspora Muslim entrepreneurs in maintaining Islamic business ethics and cultural identity while navigating increasingly competitive market environments and multicultural business interactions. In Southeast Asia, cross-border trade among ethnic communities continues to expand, yet reports of declining ethical practice and weakened cultural ties in diaspora business networks raise concerns for the sustainability of moral economic conduct. These conditions underscore the urgency to investigate how traditional Islamic values and Minangkabau customs are preserved, negotiated, and transformed within contemporary business settings. This research aims to understand the internalization of Islamic values and Minangkabau adat within the business practices of migrant traders, as well as how these values adapt to Malaysian socio-cultural contexts. Employing a qualitative method with an ethnographic approach, data were collected through in-depth interviews, participant observation, and document analysis involving 10 key informants consisting of Minangkabau traders and community leaders in Negeri Sembilan. Thematic data analysis highlights the dynamic interplay between religious principles, customary norms, and economic behavior. Findings reveal that Minangkabau traders uphold Islamic business ethics through the values of honesty, trust, and ukhuwah, while simultaneously adjusting to local business norms and regulations. Their ethical approach forms a contextual model of entrepreneurship that balances spiritual commitments with economic pragmatism. This study contributes to the formulation of the concept of Islamic Entrepreneurial Diaspora, offering an integrative model for understanding how Islamic belief systems interact with local culture in cross-national economic practices. The discovery provides theoretical enrichment to Islamic business ethics discourse and demonstrates the enduring importance of local cultural values in navigating global commercial pressures.